A case of occurring hemodynamic deterioration and ST-segment elevation during transcatheter aortic valve implantation - Oktay Ergene; Volkan Emren; Hamza Duygu; Nihan Kahya Eren (KARE Publishing, 2014)
Transcatheter aortic valve implantation is becoming increasingly popular as an alternative treatment technique for symptomatic patients with severe aortic stenosis, who are at high risk for surgery. However, with this revolutionary treatment modality, some fatal complications have also emerged. One of these fatal complications is the occlusion of the left main coronary artery at the time of procedure. In this case report, we report a case of a transcatheter aortic valve implantation complicated by acute left main trunk subtotal occlusion and hemodynamic collapse, which was successfully recovered by balloon angioplasty and stent implantation.